2017
DOI: 10.48550/arxiv.1703.07184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zero-Error Affine, Unitary, and Probabilistic OBDDs

Abstract: We introduce the affine OBDD model and show that zeroerror affine OBDDs can be exponentially narrower than bounded-error unitary and probabilistic OBDDs on certain problems. Moreover, we show that Las Vegas unitary and probabilistic OBDDs can be quadratically narrower than deterministic OBDDs. We also obtain the same results by considering the automata versions of these models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This measure is an analog of a number of states for finite automaton and OBDDs can be seen as nonuniform finite automata (see for example [4]). As for many other computation models, it is possible to consider quantum OBDDs, and during the last decade they have been studied vividly [1,5,43,48,47,2,24,23,20,19,21,31,30].…”
Section: Introductionmentioning
confidence: 99%
“…This measure is an analog of a number of states for finite automaton and OBDDs can be seen as nonuniform finite automata (see for example [4]). As for many other computation models, it is possible to consider quantum OBDDs, and during the last decade they have been studied vividly [1,5,43,48,47,2,24,23,20,19,21,31,30].…”
Section: Introductionmentioning
confidence: 99%
“…AfAs was formally defined in [7], and it was shown that they are more powerful than PFAs and quantum finite automata (QFAs) in bounded-error and unbounded-error settings, but their nondeterministic version is equivalent to nondeterministic QFAs. Since then, AfAs and their different generalizations (e.g., OBDDs and using counters) have been investigated in a series of work [28,14,22,17,29,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The computational power of AfAs and their generalizations have been examined and compared with their probabilistic and quantum counterparts in a series of papers [23,5,9,18,12,24,10,11,13,14]. In the unbounded-error and boundederror language recognition modes, AfAs are more powerful than PFAs and QFAs, where the latter models recognize all and only stochastic and regular languages, respectively [20,19,16,27,17].…”
Section: Introductionmentioning
confidence: 99%